2016
DOI: 10.1111/jpn.12419
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the suitability of maggot meal as a partial substitute of soya bean on the productive traits, digestibility indices and organoleptic properties of broiler meat

Abstract: This study was conducted to replace soya bean meal with maggot meal at difference percentages. A total of 120 one-day-old broiler chicks were divided into four groups. Four diets were formulated with maggot meal to replace soya bean meal at the rate of 0%, 10%, 20% and 30% designated as A, B, C and D respectively. Feed and water were offered ad libitum during the study which lasted for 28 days. Feed intake decreased significantly in treated groups while body weight, Feed conversion ratio and dressing percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 23 publications
11
46
0
1
Order By: Relevance
“…Findings of the current study are in the line with the results of Khan et al. () and Okah and Onwujiarir () who concluded that feed intake was decreased in the group fed maggot meal in the ration. Poorghasemi et al.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Findings of the current study are in the line with the results of Khan et al. () and Okah and Onwujiarir () who concluded that feed intake was decreased in the group fed maggot meal in the ration. Poorghasemi et al.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Okah and Onwujiarir () and Khan et al. () also reported significantly higher weight gain in birds offered with insect meal (maggot meal).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations